PERHITUNGAN TIANG PANCANG PADA PELAKSANAAN PEMBANGUNAN JEMBATAN MARGOMULYO DI KOTA BALIKPAPAN PADA DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN TIMUR - RIYANTO, FAJAR (KURVA S JURNAL MAHASISWA, 2014)
The purpose of this study among others, is to calculate the burden borne on poles,calculate the bearing capacity of piles based on the data and calculate iron sondir andcalculate the bearing capacity of piles based on the data kalendering. This research wasconducted in the city of Balikpapan Village Margomulyo from June 2012 to October 2012.Methods of analysis of data on the burden borne bridge piling using the method of dataKalendering Hilley and Danish Formula and method of data Sondir with Meyerhoff and ENDBearings and Friction. The data collected are then analyzed to determine how much load iscarried by the bridge piles. The results of the calculation of the bearing capacity of piles ofdata sondir: point (S - 1) Meyerhoff: 41.09 tons, END Bearing and Friction Pile: 40.89 tons;point (S - 2) Meyerhoff: 43.12 tons, END Bearings and friction Pile: 47.85 tons; point (S - 3)Meyerhoff: 45.14 tons, END Bearing and friction Pile: 51.66 tons. Results calculated fromthe data piling kalendering: (Kalendering 1) Method Hilley: 144.79 tons, Method Danish:142.98 tons, Method Benabencq: 221.64 tons; (Kalendering 2) Method Hilley: 111.38 tons,Method Danish: 112.73 tons, 122.09 tons Benabencq method; (Kalendering 3) MethodsHilley: 115.61 tons, method Danish: 104.57 tons, method Benabencq: 104.87 tons.